Pengaruh Daun Tanaman dalam Pemeraman terhadap Perkembangan Antraknos pada Pisang Ambon - Toekidjo Martoredjo; Wahyu Budiasih; Ambarwati Harsojo Tjokrosoedarmo (Universitas Gadjah Mada, 1998)
Using plant leaves such as banana leaves, glyricidia leaves, and rice straw for ripening resulted in lower ripening stage score than control or using chemical such as ethrel, although statistically they are not siginificantly different. Glyricidia leaves and rice straw inhibit disease symptom representing anthracnose (Colletotrichum musae) development on Gros-Michel banana.